GAMBARAN PENGETAHUAN IBU DAN SUAMI TENTANG PERUBAHAN FISIK DAN PSIKOLOGIS SAAT HAMIL DI WILAYAH KERJA PUSKESMAS BERINGIN RAYA KOTA BENGKULUTAHUN 2016 - Nelazyani, Lucky; Hikmi, Hailul (Journal Of Midwifery, 2018)
Pregnancy involved various physical and psychological changes. Pregnancy usually develop normally, but sometimes not as expected, it was difficult to predict whether pregnant women could be problematic during pregnancy or fine. Thus the understanding of the mother and husband in the face of physical and psychological changes was very important. This study aimed to describe the understanding of mother and husband toward physical and psychological changes during pregnancy in working area of Beringin Raya Public Health Center Bengkulu 2016.The method used in this research was a descriptive study, with the number of respondents 82 pregnant women and 82 respondents husband was taken with purposive sampling technique. Data used in this study using primary data and analyzed using univariate analysis.More than half of pregnant women (56.1%), had less understanding about the physiological changes during pregnancy, most pregnant women (46.3%), had a good understanding about the physiological changes during pregnancy. more than half of pregnant husband (56.1%), had less understanding about the physiological changes in pregnant women and pregnant husband half (50.0%), had less understanding about the physiological changes of pregnant women.Expectant mothers and wives understanding about physical and psychological changes in the poor category. Beringin Raya Public Health Center Bengkulu could further increase in outreach to pregnant women thus increasing understanding of pregnant women.